(untitled) (Community Based Medical Journal, 2026)
Biliary atresia is a rare but devastating progressive cholangiopathy and is the leading cause of liver transplantation in children. The key to a better prognosis and the success of the Kasai portoenterostomy (HPE) procedure is early diagnosis and timely surgical intervention ideally before 60 days of life. This case report aims to highlight the diagnostic process and challenges in confirming biliary atresia (BA) in a jaundice neonate. Diagnosing biliary atresia (BA) can be challenging as its early symptoms often overlap with more common benign causes of neonatal jaundice. The definitive diagnosis depends on clinical presentation, laboratory results, imaging studies (specifically the USG findings of an atrophic gallbladder or triangular cord sign) and ultimately an intraoperative cholangiogram. This case emphasizes the critical need for vigilance and a high index of suspicion in any infant with persistent conjugated hyperbilirubinemia. CBMJ 2026 January: vol. 15 no. 01 P:249- 252